India’s Non-Traditional Security Policy: Nexus between Energy And Climate Change - Zomuanthanga , JC; Sailo, Lalramliani (Journal of Ecohumanism, 2025)
The energy sector is the largest emitter of GHGs contributing to climate change. Energy and climate change are two dominant concerns for a developing country like India. There lies a dilemma between the need for increased energy use for development and limiting or mitigating emissions from fossil fuels, which brought the importance of energy security while dealing with climate change. India’s response to climate change is guided by its national plans, programs, and priorities and not much by the influence of international actors. Due to its hasty formation and the lengthy approval process, the National Action Plan on Climate Change (NAPCC) proved inadequate and requires continuous efforts to promote strategic policies. The country’s strategy to face the changing climate must be mission-focused and target-oriented with a strong political will to achieve sustainable development. In turn, energy security will bring national security.